Desafíos éticos de la comunicación en la Carta de Santiago - Estévez López, Elisa (Cauriensia, 2022)
Speech-ethics is one of the central concerns of the letter of James (Jas. 1:19-20.26; 2:12; 3:1-12; 4:1-2.11-12; 5:9.12). He uses it to warn against assimilation to conventional values and to set the limits of Judeo-Christian identity (use of a varied vocabulary from the semantic field of purity-impurity). The ethical behaviour approved by James concerning speech are not detached from his concern for the treatment of the poor, nor from the thoughts, emotions, desires, etc. that are born of the heart. This article uses the zones of interaction personality model proposed by Bernard de Gerardon to show the interrelationship between the zone of self-expressive speech (mouth-ears), emotion-fused thought (eyes-heart) and purposeful action (hands-feet) in James' letter. This perspective makes it possible to understand the regulation of the use of language according to the unitary conception of the human being in biblical thought and to understand this Christian writing in a more holistic way.